1951
DOI: 10.1121/1.1906787
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interaural Phase on Masked Thresholds I. The Role of Interaural Time-Deviation

Abstract: When a narrow band of noise, of constant level (the signal) is masked by a wider band of noise (the masker), the amount of noise required to drown out the signal often depends significantly upon the interaural phase relations of signal and masker. Thus, more masking noise is required if the signal is 180° out of phase at the two ears than if it is in phase: provided that the masker remains in phase. The out-of-phase signal, in other words, shows an advantage in audibility. The advantage is very striking for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…For most complex stimuli with time-varying amplitudes, the modulation depth also changes over time, thus both ILD and ITD cues will contribute to the SIED cue at different points within the stimulus. The dominance of ITD over ILD in predicting binaural detection results is consistent with the studies by van der Heijden and Joris (2010) and Webster (1951).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For most complex stimuli with time-varying amplitudes, the modulation depth also changes over time, thus both ILD and ITD cues will contribute to the SIED cue at different points within the stimulus. The dominance of ITD over ILD in predicting binaural detection results is consistent with the studies by van der Heijden and Joris (2010) and Webster (1951).…”
Section: Discussionsupporting
confidence: 81%
“…His results show that at low SNR, listeners have significantly lower discrimination thresholds under dichotic conditions than under diotic conditions; at high SNR, listeners have similar discrimination thresholds for the two conditions. Henning further demonstrated that results from the amplitude-modulation discrimination task could be predicted using Durlach's EC model (Durlach, 1963) and the Webster-Jeffress models (Webster, 1951). The SIED cue provides an alternative explanation for results from amplitude-modulation discrimination because envelope cues are available for the modulated stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…They are the cross-correlation (CC) model (Osman, 1971(Osman, , 1973, the equalization-cancellation (EC) model (Durlach, 1963), and interaural difference models (e.g., Webster, 1951;Hafter, 1971) that utilize ITDs and/or interaural level differences (ILDs) in various ways. The models, which started as essentially "black-box" models, have become more physiologically motivated over the years.…”
Section: Introductionmentioning
confidence: 99%
“…For normal-hearing (NH) listeners, binaural hearing provides advantages for speech reception in noise and for signal detection (Webster, 1951;Schubert, 1956;Carhart et al, 1967;Bronkhorst and Plomp, 1988;Lavandier and Culling, 2010). One advantage, referred to as "binaural unmasking," can be observed when one compares listeners' performance in a diotic condition in which the target has the same interaural configuration as the noise, to a dichotic condition in which the target and noise have different interaural configurations.…”
Section: Introductionmentioning
confidence: 99%